Scaling Digital Fisheries Management: The Role of e-PIT in Enhancing Data Accuracy and Operational Efficiency - Suherman, Agus; Nurul Huda, Hamdan; Timilsina, Raja Rajendra; Hernuryadin, Yayan; Untoro, Firli; Amboro, R. Tono; Sock, Fatou; Koirala, Pankaj (Jurnal Ilmiah Perikanan dan Kelautan, 2025)
Graphical Abstract   Highlight Research The implementation of e-PIT in Indonesia's fisheries governance led to a 475% increase in vessel arrivals from 2022 to 2024. Catch showed a 210% increase in 2024, reaching 1.167 billion kilograms, compared to 2023. The system enabled 161% growth in PHP revenue collection, from Rp 590.85 billion in 2023 to Rp 951.64 billion in 2024. A security evaluation (Pentest) of e-PIT revealed vulnerabilities, and effective security enhancements were made to ensure system reliability and scalability.     Abstract The e-PIT system has transformed fisheries management in Indonesia by improving data accuracy, efficiency, and transparency. This study examines the effects of e-PIT from 2022 to 2024, focusing on metrics such as vessel arrivals, catch data, and PHP revenue. A descriptive-exploratory approach was used to compare data before and after e-PIT's implementation. Findings show significant progress: vessel arrivals rose by 475%, catch amounts doubled to 1.167 billion kilograms, and PHP revenue increased by 161% to Rp 951.64 billion in 2024. Daily operations stabilized, with 257 transactions worth IDR 2.6 billion. While a security test found some vulnerabilities like unsecured cookies and outdated server settings, improvements have been made to enhance security, aligning with standards like ISO/IEC 27001. These measures ensure e-PIT's security, scalability, and reliability as a model for digital fisheries governance. The study concludes that e-PIT boosts efficiency, accuracy, and transparency. Recommendations include improving digital infrastructure, cybersecurity, and stakeholder engagement. Despite its focus on specific data and regions, the study offers insights for applying e-PIT in other developing countries, supporting global goals like SDG 14 and the FAO Fisheries Governance Framework.